Hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material as well as preparation method and application thereof

By preparing photothermal conversion materials with hydrophilic-hydrophobic anisotropic composite structure, combining Fe3O4-PDA nanocomposites and hydrophilic sponges, the problems of low moisture transfer efficiency and salt deposition in seawater desalination are solved, and efficient photothermal conversion and seawater desalination performance are achieved, with good stability and antibacterial effects.

CN120464018APending Publication Date: 2025-08-12QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510799571.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

During the desalination of seawater, existing photothermal conversion materials have problems such as low moisture transfer efficiency and blockage caused by surface salt deposition. In addition, traditional materials have high cost and poor stability, making them difficult to apply on a large scale.

Method used

By preparing photothermal conversion materials of hydrophilic-hydrophobic anisotropic composite structures, the Fe3O4-PDA nanocomposite is combined with a hydrophilic sponge substrate with a hydrophilic sponge substrate to improve the photothermal conversion performance, and avoid salt deposition through hydrophobic modification of the sponge surface to form a self-floating interface.

Benefits of technology

It realizes efficient moisture transfer and light-heat conversion, improves solar energy utilization efficiency, prevents salt deposition, has excellent seawater desalination performance and antibacterial effect, is low-cost and suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120464018A_ABST
    Figure CN120464018A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material as well as a preparation method and application thereof, and relates to the technical field of photothermal conversion materials. The prepared photo-thermal conversion particle Fe3O4-PDA nano-composite is combined with the hydrophilic sponge substrate through the hydrophobic binder, the prepared Fe3O4-PDA nano-composite has excellent photo-thermal conversion performance, the hydrophilic sponge provides a path for effective transmission of water, meanwhile, the porous structure of the hydrophilic sponge can effectively trap light, and the hydrophilic sponge can be used for preparing the photo-thermal conversion material. The solar energy utilization efficiency is improved; and partial hydrophobic modification on the surface of the sponge can effectively reduce surface salt deposition, and in addition, the surface hydrophobic structure provides favorable conditions for sponge interface self-floating and formation of a solar photo-thermal interface evaporation system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photothermal conversion materials, and in particular to a photothermal conversion material with a hydrophilic-hydrophobic anisotropic composite structure, a preparation method thereof, and applications thereof. Background Art

[0002] In the process of globalization, the problem of energy shortage caused by population explosion and rapid economic development is becoming increasingly serious. The energy supply shortage caused by the gradual reduction of traditional non-renewable resources, the increasing difficulty and cost of mining has not only seriously affected industrial production, but also seriously restricted the sustained growth of the economy. As a clean and renewable energy source, solar energy is considered to be an effective alternative to traditional energy due to its large natural reserves, wide radiation range, and the need for transportation. Solar thermal conversion, as an effective form of solar energy utilization, is widely used in energy, batteries, and the environment. At present, solar-driven photothermal interface water treatment technology can not only reduce heat loss during the use of materials and improve the efficiency of solar energy utilization, but also effectively improve sewage treatment effects. It is widely used in wastewater treatment and seawater desalination.

[0003] Studies have shown that the main factors affecting the efficiency of solar energy utilization and sewage treatment efficiency include solar energy absorption efficiency, water transfer efficiency during the photothermal process, and heat loss during the use of materials. The earliest precious metal photothermal particles represented by gold could not be put into practical use due to their high cost and easy agglomeration. Biochar materials are simple to prepare and have abundant sources. They have great application potential in the field of light absorption, but they have obvious individual differences and are difficult to be applied in large-scale industrial applications. As a stable inorganic material, metal oxides have been widely studied and applied in scenarios such as photothermal evaporation and seawater purification due to their mature preparation methods, controllable morphology, and diverse types.

[0004] In recent years, solar thermal interfacial evaporation has proven to be an effective alternative to traditional bulk heating and has been widely used in solar thermal wastewater treatment and seawater desalination. Research has found that good hydrophilicity is a prerequisite for effective water transfer. However, during the desalination process, rapid surface water evaporation can lead to crystalline salts blocking the transfer channels on the evaporator surface, causing scaling and compromising the durability of the material. Research has found that hydrophobic modification can effectively alleviate this problem and improve material stability. Recent biomimetic research has revealed that organisms in nature evolve near-perfect structures to adapt to environmental changes. Incorporating biomimetic thinking into material design and preparation can effectively improve material stability and efficiency. The anisotropic surfaces of lotus leaves in nature offer inspiration for the functionalization of material surfaces. The development of materials with a hydrophilic-hydrophobic combination can not only ensure efficient water transfer but also avoid surface salt deposition, offering promising solutions for addressing the low conversion efficiency and wastewater treatment capacity of solar thermal conversion materials. Currently, there are no reports of effective photothermal conversion materials based on anisotropic hydrophilic-hydrophobic composite structures. Summary of the Invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the existing technology, to provide a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material and its preparation method and application, and to combine the prepared photothermal conversion particle Fe3O4-PDA nanocomposite with a hydrophilic sponge base through a hydrophobic binder, wherein the prepared Fe3O4-PDA nanocomposite has excellent photothermal conversion performance, and the hydrophilic sponge provides a path for the effective transmission of water. At the same time, its porous structure can effectively trap light and improve the efficiency of solar energy utilization; and the partial hydrophobic modification of the sponge surface can effectively reduce surface salt deposition. In addition, the surface hydrophobic structure provides favorable conditions for the self-floating of the sponge interface and the formation of a solar thermal interface evaporation system.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material, comprising the following steps:

[0008] S1 prepared Fe3O4 nanoparticles by hydrothermal method;

[0009] S2 disperses Fe3O4 nanoparticles in a solvent to obtain a Fe3O4 dispersion;

[0010] S3: adding dopamine hydrochloride to the Fe3O4 dispersion and stirring at room temperature to allow for a full reaction;

[0011] After the reaction in S4 is completed, the product is washed and dried to collect the product Fe3O4-PDA nanocomposite;

[0012] S5: dispersing the hydrophobic binder in an organic solvent to obtain a mixed solution A, then adding the product obtained in step S4 to the mixed solution A, and ultrasonically dispersing to obtain a mixed solution B;

[0013] S6 pre-treats the hydrophilic sponge to obtain a clean sponge base;

[0014] S7: immersing the sponge base in the mixed solution B obtained in step S5, drying it, and then punching holes in the hydrophilic area of the sponge base with a needle to obtain a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material.

[0015] Preferably, in step S2, the solvent is a Tris-HCl buffer solution, the concentration of the Fe3O4 dispersion is 0.05-0.25 mg / mL, and the pH is 8-9.

[0016] Preferably, in step S3, the mass ratio of dopamine hydrochloride to Fe3O4 nanoparticles is (1-10):1; and the stirring time is 1-2h.

[0017] Preferably, in step S4, the solvent used for washing is deionized water, the drying temperature is 40-50° C., and the drying time is 4-8 hours.

[0018] Preferably, in step S5, the hydrophobic binder is polydimethylsiloxane (PDMS), polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); the organic solvent is ethanol, methanol, isopropanol or tetrahydrofuran; the mass ratio of the organic solvent to the hydrophobic binder is (5-10):1; in the mixed solution B, the concentration of the Fe3O4-PDA nanocomposite is 2-5 mg / mL; and the ultrasonic time is 20-40 min.

[0019] Preferably, in step S6, the hydrophilic sponge is made of polyurethane (PU), polyvinyl alcohol (PVA) or melamine (MEL); the pretreatment process of the hydrophilic sponge is: placing the hydrophilic sponge in ethanol, ultrasonically treating it for 20-40 minutes, and repeating the process 3-5 times; then placing it in deionized water, ultrasonically treating it for 20-40 minutes, and repeating the process 3-5 times; finally, taking out the hydrophilic sponge and drying it to obtain a clean sponge base.

[0020] Preferably, in step S6, the clean sponge base is cut into cylinders with a radius of 0.5-2.5 cm and a height of 1-2 cm.

[0021] Preferably, in step S7, the amount of mixed solution B is 10-15 mL; the drying temperature is 40-60° C., and the drying time is 2-6 h.

[0022] In a second aspect, the present invention provides a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material, which is prepared by the above-mentioned method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material.

[0023] In a third aspect, the present invention provides an application of the above-mentioned hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material, and applies the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material in the fields of solar thermal water evaporation, seawater desalination, and antibacterial.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention utilizes a mixture of a hydrophobic binder and photothermal conversion particles to obtain a surface coating solution, which is then partially modified onto a hydrophilic sponge substrate to produce a photothermal conversion sponge material with hydrophilic-hydrophobic anisotropy. Fe3O4 nanoparticles serve as the photothermal conversion material to convert light energy into thermal energy. Dopamine hydrochloride primarily serves the following functions: first, it acts as a stabilizing layer for the Fe3O4 nanoparticles, preventing them from over-oxidizing; second, it possesses excellent photothermal conversion performance, and in combination with the Fe3O4 nanoparticles, it can enhance the photothermal evaporation performance of the system. The hydrophobic binder achieves hydrophilic-hydrophobic anisotropy on both sides of the sponge. The unmodified hydrophilic side of the sponge facilitates water transfer to the reaction interface, while the hydrophobic side allows for self-floating of the evaporator and effectively avoids surface salt deposition. The resulting composite structure, obtained after perforation of the sponge, effectively traps light, improving solar energy utilization efficiency, and facilitates the directional transfer of water, preventing excessive salt accumulation, thereby achieving stable operation of the evaporator. The hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material prepared by the present invention has excellent photothermal conversion performance and seawater desalination performance. The evaporation efficiency of pure water under the intensity of one sun can reach 1.12 kg·m -2 ·h -1 The simulated seawater desalination rate can reach 0.99 kg·m -2 ·h -1 , and there is no obvious salt deposition on the material surface. Furthermore, the hydrophilic-hydrophobic anisotropic composite photothermal conversion material prepared by the present invention has excellent bactericidal efficacy, achieving 100% bactericidal efficiency against both Escherichia coli and Staphylococcus aureus after 2 hours of irradiation under simulated sunlight conditions. The hydrophilic-hydrophobic anisotropic composite photothermal conversion material prepared by the present invention has the advantages of low cost, simple preparation, high performance, and good cyclic stability, and has broad application prospects in environmental purification and photothermal conversion.

[0026] 2. This invention features simple equipment, easy operation, good scalability and plasticity of the substrate, and the readily available, inexpensive chemical reagents used, along with good reproducibility, making it suitable for mass production. The hydrophilic-hydrophobic anisotropic sponge prepared by this invention exhibits excellent scalability, stability, and ease of operation, making it suitable for applications such as solar-powered water evaporation and high-concentration seawater desalination, as well as for treating wastewater containing bacteria. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : is a SEM photo of a hydrophilic sponge and a Janus sponge @ Fe3O4-PDA photothermal conversion material prepared in Example 1 of the present invention, wherein Figure 1 a. Figure 1 b. Figure 1 c are SEM photos of hydrophilic sponge at different magnifications, Figure 1 d. Figure 1 e. Figure 1 f are SEM photos of the hydrophobic surface of the Janus sponge@Fe3O4-PDA photothermal conversion material in Example 1 at different magnifications.

[0028] Figure 2 The contact angle photos of the hydrophilic sponge and the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 1 of the present invention are shown in FIG. Figure 2 a is a photo of the contact angle of the hydrophilic surface of the hydrophilic sponge. Figure 2 b is a contact angle photograph of the hydrophobic surface of the Janus sponge@Fe3O4-PDA photothermal conversion material in Example 1.

[0029] Figure 3 This is a test chart of the photothermal conversion performance of the Janus sponge @Fe3O4-PDA photothermal conversion material prepared in Example 1 of the present invention under one sunlight intensity, wherein Figure 3 a is the evaporation rate of pure water, Figure 3 b is the simulated seawater evaporation rate, Figure 3 c is the evaporation rate of 30 wt.% brine.

[0030] Figure 4 These are the antibacterial performance test diagrams of the Janus sponge @Fe3O4-PDA photothermal conversion material prepared in Example 1 of the present invention, wherein Figures a, b, and c are antibacterial tests conducted on Escherichia coli, Figure a is a blank control group, Figure b is a group using a hydrophilic sponge, and Figure c is a group using the Janus sponge @Fe3O4-PDA photothermal conversion material in Example 1; Figures d, e, and f are antibacterial tests conducted on Staphylococcus aureus, Figure d is a blank control group, Figure e is a group using a hydrophilic sponge, and Figure f is a group using the Janus sponge @Fe3O4-PDA photothermal conversion material in Example 1. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0032] Example 1

[0033] The method for preparing the hydrophilic-hydrophobic anisotropic composite structure light-to-heat conversion material of this embodiment includes the following steps:

[0034] S1 prepared Fe3O4 nanoparticles by a hydrothermal method: 0.5 g of ferric chloride hexahydrate, 0.5 g of polyethylene glycol 1000 monomethyl ether (MPEG 1000), and 1.8 g of sodium acetate trihydrate were weighed and placed in 50 mL of ethylene glycol. The mixture was sonicated for 0.5 h to fully dissolve the mixture. The resulting solution was poured into a reactor and heated at 200°C for 10 h to obtain Fe3O4 nanoparticles.

[0035] S2: 30 mg of Fe3O4 nanoparticles were dispersed in Tris-HCl buffer solution to obtain 250 mL of 0.12 mg / mL Fe3O4 dispersion, and the pH was adjusted to 8.5 with 0.1 mol / L NaOH solution;

[0036] S3: Add 125 mg of dopamine hydrochloride to the Fe3O4 dispersion and stir at room temperature for 1 h to allow it to react fully;

[0037] After the reaction is completed, the product is washed with deionized water and then dried at 45 ° C for 4 h to collect the product Fe3O4-PDA nanocomposite;

[0038] S5: 1 g of PDMS was dispersed in 10 mL of ethanol to obtain a mixed solution A. 30 mg of Fe3O4-PDA nanocomposite was then added to the mixed solution A and ultrasonically dispersed for 20 min to obtain a mixed solution B.

[0039] S6: Place the hydrophilic PU sponge in ethanol and ultrasonically treat it for 20 minutes, repeating this process three times; place the ethanol-treated sponge in deionized water again and ultrasonically treat it for 20 minutes, repeating this process three times; finally, take out the sponge and dry it to obtain a clean sponge base, which is then cut into cylinders with a radius of 1.5 cm and a height of 1 cm;

[0040] S7: The sponge substrate is immersed in the mixed solution B, and then dried at 60°C for 2 h. Then, a needle is used to perforate the hydrophilic area of the sponge substrate, with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material Janus sponge @Fe3O4-PDA.

[0041] Example 2

[0042] S1 prepares Fe3O4 nanoparticles by a hydrothermal method, and the specific preparation process is the same as that in Example 1;

[0043] S2: 12.5 mg of Fe3O4 nanoparticles were dispersed in Tris-HCl buffer solution to obtain 250 mL of 0.05 mg / mL Fe3O4 dispersion, and the pH was adjusted to 8 with 0.1 mol / L NaOH solution;

[0044] S3: Add 125 mg of dopamine hydrochloride to the Fe3O4 dispersion and stir at room temperature for 2 h to allow it to react fully;

[0045] After the reaction is completed, the product is washed with deionized water and then dried at 40 ° C for 8 h to collect the product Fe3O4-PDA nanocomposite;

[0046] S5: 1 g of PVDF was dispersed in 10 mL of methanol to obtain a mixed solution A. 20 mg of Fe3O4-PDA nanocomposite was then added to the mixed solution A and ultrasonically dispersed for 30 min to obtain a mixed solution B.

[0047] S6: Place the hydrophilic PVA sponge in ethanol and ultrasonically treat it for 30 minutes, repeating this process three times; place the ethanol-treated sponge in deionized water again and ultrasonically treat it for 30 minutes, repeating this process three times; finally, take out the sponge and dry it to obtain a clean sponge base, which is then cut into cylinders with a radius of 1.5 cm and a height of 1 cm;

[0048] S7: The sponge substrate is immersed in the mixed solution B, and then dried at 50°C for 5 h. Then, a needle is used to perforate the hydrophilic area of the sponge substrate, with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material Janus sponge @Fe3O4-PDA.

[0049] Example 3

[0050] S1 prepares Fe3O4 nanoparticles by a hydrothermal method, and the specific preparation process is the same as that in Example 1;

[0051] S2: 62.5 mg of Fe3O4 nanoparticles were dispersed in Tris-HCl buffer solution to obtain 250 mL of 0.25 mg / mL Fe3O4 dispersion, and the pH was adjusted to 9 by adding 0.1 mol / L NaOH solution;

[0052] S3: Add 125 mg of dopamine hydrochloride to the Fe3O4 dispersion and stir at room temperature for 1 h to allow it to react fully;

[0053] After the reaction is completed, the product is washed with deionized water and dried at 50 ° C for 5 h to collect the product Fe3O4-PDA nanocomposite;

[0054] S5: 1 g of PTFE was dispersed in 10 mL of isopropanol to obtain a mixed solution A. 50 mg of Fe3O4-PDA nanocomposite was then added to the mixed solution A and ultrasonically dispersed for 40 min to obtain a mixed solution B.

[0055] S6: The hydrophilic MEL sponge was placed in ethanol and ultrasonically treated for 40 minutes, and the process was repeated three times; the ethanol-treated sponge was placed in deionized water again and ultrasonically treated for 40 minutes, and the process was repeated three times; finally, the sponge was taken out and dried to obtain a clean sponge base, which was then cut into a cylinder with a radius of 1.5 cm and a height of 1 cm;

[0056] S7: The sponge substrate is immersed in the mixed solution B, and then dried at 40 °C for 6 h. Then, a needle is used to perforate the hydrophilic area of the sponge substrate, with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material Janus sponge @Fe3O4-PDA.

[0057] Comparative Example 1

[0058] The preparation method of the photothermal conversion material of Comparative Example 1 comprises the following steps:

[0059] S1: 1 g of PDMS was dispersed in 10 mL of ethanol to obtain a mixture A. 30 mg of PDA was then added to the mixture A and ultrasonically dispersed for 20 min to obtain a mixture B.

[0060] S2: Place the hydrophilic PU sponge in ethanol and ultrasonically treat it for 20 minutes, repeating this process three times; place the ethanol-treated sponge in deionized water again and ultrasonically treat it for 20 minutes, repeating this process three times; finally, take out the sponge and dry it to obtain a clean sponge base, which is then cut into cylinders with a radius of 1.5 cm and a height of 1 cm;

[0061] S3 immersed the sponge substrate in the mixed solution B, then dried it at 60°C for 2 h, and then used a needle to perforate the hydrophilic area of the sponge substrate with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the photothermal conversion material Janus sponge@PDA.

[0062] Comparative Example 2

[0063] The preparation method of the photothermal conversion material of Comparative Example 2 comprises the following steps:

[0064] S1 prepares Fe3O4 nanoparticles by a hydrothermal method, and the specific preparation process is the same as that in Example 1;

[0065] S2: 1 g of PDMS was dispersed in 10 mL of ethanol to obtain a mixture A. 30 mg of Fe3O4 nanoparticles were then added to the mixture A and ultrasonically dispersed for 20 min to obtain a mixture B.

[0066] S3: Place the hydrophilic PU sponge in ethanol and ultrasonically treat it for 20 minutes, repeating this process three times; place the ethanol-treated sponge in deionized water again and ultrasonically treat it for 20 minutes, repeating this process three times; finally, take out the sponge and dry it to obtain a clean sponge base, which is then cut into cylinders with a radius of 1.5 cm and a height of 1 cm;

[0067] S4 immersed the sponge substrate in the mixed solution B, then dried it at 60°C for 2 h, and then used a needle to perforate the hydrophilic area of the sponge substrate with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the photothermal conversion material Janus sponge@Fe3O4.

[0068] Comparative Example 3

[0069] The preparation method of the photothermal conversion material of Comparative Example 3 comprises the following steps:

[0070] S1 prepares Fe3O4 nanoparticles by a hydrothermal method, and the specific preparation process is the same as that in Example 1;

[0071] S2: 30 mg of Fe3O4 nanoparticles were dispersed in Tris-HCl buffer solution to obtain 250 mL of 0.12 mg / mL Fe3O4 dispersion, and the pH was adjusted to 8.5 with 0.1 mol / L NaOH solution;

[0072] S3: Add 125 mg of dopamine hydrochloride to the Fe3O4 dispersion and stir at room temperature for 1 h to allow it to react fully;

[0073] After the reaction is completed, the product is washed with deionized water and then dried at 45 ° C for 4 h to collect the product Fe3O4-PDA nanocomposite;

[0074] S5: 30 mg of Fe3O4-PDA nanocomposite was added to 10 mL of ethanol and ultrasonically dispersed for 20 min to obtain mixed solution A;

[0075] S6: Place the hydrophilic PU sponge in ethanol and ultrasonically treat it for 20 minutes, repeating this process three times; place the ethanol-treated sponge in deionized water again and ultrasonically treat it for 20 minutes, repeating this process three times; finally, take out the sponge and dry it to obtain a clean sponge base, which is then cut into cylinders with a radius of 1.5 cm and a height of 1 cm;

[0076] S7: The sponge substrate is immersed in the mixed solution A, and then dried at 60°C for 2 h. Then, a needle is used to perforate the hydrophilic area of the sponge substrate, with a pore size of 500 μm and a perforation density of 36 per cm 2 , and obtained the photothermal conversion material Janus sponge@Fe3O4-PDA.

[0077] Comparative Example 4

[0078] The difference from Example 1 is that in step S7, no holes are punched on the sponge base.

[0079] The performance of the light-to-heat conversion materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested:

[0080] A 25 mL beaker was filled with 20 mL of water. A piece of the photothermal conversion material prepared in Examples 1-3 and Comparative Examples 1-4 was floated on the water surface. A glass cover was placed outside to collect the condensed water. At 25°C and 30% RH, the condensed water was collected at 1 kW·m -2 Solar water evaporation experiments were conducted under simulated sunlight. An electronic analytical balance was used to monitor the change in water mass during evaporation and calculate the evaporation rate. The desalination rate was calculated by replacing the water with simulated seawater and 30wt.% high-concentration salt water.

[0081] In addition, each photothermal conversion material was used for solar photothermal water evaporation of aqueous solution containing Escherichia coli and Staphylococcus aureus. The experiment was conducted with bacteria in logarithmic growth phase, and the bacterial concentration was 10 5 CFU / mL, 200 μL of the original bacterial solution and the bacterial solution in the beaker after 2 h of illumination were respectively taken for plate coating, followed by overnight culture for 12 h to evaluate the bactericidal effect.

[0082] like Figure 1 As shown in the figure, the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 1 has a typical porous structure, and the unmodified sponge in the lower layer has a macroporous network structure. Figure 1 In c, the fiber surface presents a smooth structure; the structure of the pores in the upper layer does not change significantly after modification. Figure 1 It can be clearly seen in f that the fiber surface has a relatively rough structure and the photothermal nanoparticles are successfully modified inside the sponge.

[0083] like Figure 2 As shown, the water contact angle picture of the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 1: Figure 2 a is the unmodified lower surface of the sponge, with a contact angle of 52°, indicating typical hydrophilicity; Figure 2 b is the modified upper surface of the sponge, with a contact angle of 139°, showing typical hydrophobicity.

[0084] like Figure 3 As shown in Figure 1, the pure water evaporation rate of the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 1 is 1.12 kg·m -2 ·h -1 The simulated desalination rate is 0.99 kg·m -2 ·h -1 The desalination rate of 30wt.% brine is 0.83kg·m -2 ·h -1 The results are about 4 times that of the unmodified hydrophilic sponge. The results show that the Janus sponge@Fe3O4-PDA photothermal conversion material prepared by the present invention has excellent photothermal conversion performance.

[0085] like Figure 4 As shown, the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 1 has excellent antibacterial properties: after irradiation for 2 hours under simulated sunlight conditions, the bactericidal efficiency against Escherichia coli and Staphylococcus aureus is 100%.

[0086] The pure water evaporation rate of the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 2 was 3.2 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 95%. The pure water evaporation rate of the Janus sponge@Fe3O4-PDA photothermal conversion material prepared in Example 3 was 3.6 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 100%.

[0087] The pure water evaporation rate of the photothermal conversion material prepared in Comparative Example 1 was 1.2 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 70%. The pure water evaporation rate of the photothermal conversion material prepared in Comparative Example 2 was 2.8 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 80%. The pure water evaporation rate of the photothermal conversion material prepared in Comparative Example 3 was 2 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 75%. The pure water evaporation rate of the photothermal conversion material prepared in Comparative Example 4 was 3.2 times that of the unmodified hydrophilic sponge, and the inactivation rate against Escherichia coli and Staphylococcus aureus was 95%.

[0088] From the above, it can be seen that compared with Example 1, no Fe3O4 nanoparticles were added in Comparative Example 1. The lack of photothermal components makes it impossible for the system to achieve good photothermal conversion performance, thereby affecting the interfacial water evaporation and antibacterial performance. Dopamine hydrochloride was not added in Comparative Example 2, that is, the surface of the Fe3O4 nanoparticles was not coated with PDA, and the oxidation reaction of the Fe3O4 nanoparticles under strong light could not be avoided, thereby causing the water evaporation and antibacterial performance of the photothermal system to decrease. In Comparative Example 3, no hydrophobic binder was added, and a hydrophilic-hydrophobic anisotropic sponge material could not be obtained. The lack of a hydrophobic side made it impossible for the evaporator to achieve self-floating, and the interfacial evaporation performance was significantly reduced. In Comparative Example 4, the sponge was not perforated, and a porous composite structure could not be obtained, which reduced the light trapping capacity and water transfer rate of the evaporator, further affecting the photothermal water evaporation and antibacterial performance.

Claims

1. A method for preparing a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material, characterized in that: The following steps are involved: S1 prepared Fe3O4 nanoparticles by hydrothermal method; S2 disperses Fe3O4 nanoparticles in a solvent to obtain a Fe3O4 dispersion; S3: adding dopamine hydrochloride to the Fe3O4 dispersion and stirring at room temperature to allow for a full reaction; After the reaction in S4 is completed, the product is washed and dried to collect the product Fe3O4-PDA nanocomposite; S5: dispersing the hydrophobic binder in an organic solvent to obtain a mixed solution A, then adding the product obtained in step S4 to the mixed solution A, and ultrasonically dispersing to obtain a mixed solution B; S6 pre-treats the hydrophilic sponge to obtain a clean sponge base; S7: immersing the sponge base in the mixed solution B obtained in step S5, drying it, and then punching holes in the hydrophilic area of the sponge base with a needle to obtain a hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material.

2. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1, wherein: In step S2, the solvent is a Tris-HCl buffer solution, the concentration of the Fe3O4 dispersion is 0.05-0.25 mg / mL, and the pH is 8-9.

3. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1, wherein: In step S3, the mass ratio of dopamine hydrochloride to Fe3O4 nanoparticles is (1-10):1; and the stirring time is 1-2h.

4. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1, wherein: In step S4, the washing solvent is deionized water, the drying temperature is 40-50° C., and the drying time is 4-8 hours.

5. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1, wherein: In step S5, the hydrophobic binder is polydimethylsiloxane, polyvinylidene fluoride or polytetrafluoroethylene; the organic solvent is ethanol, methanol, isopropanol or tetrahydrofuran; the mass ratio of the organic solvent to the hydrophobic binder is (5-10):1; in the mixed solution B, the concentration of the Fe3O4-PDA nanocomposite is 2-5 mg / mL; and the ultrasonic time is 20-40 min.

6. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1, wherein: In step S6, the hydrophilic sponge is made of polyurethane, polyvinyl alcohol or melamine; the pretreatment process of the hydrophilic sponge is: placing the hydrophilic sponge in ethanol, ultrasonically treating it for 20-40 minutes, and repeating this process 3-5 times; then placing it in deionized water, ultrasonically treating it for 20-40 minutes, and repeating this process 3-5 times; finally, taking out the hydrophilic sponge and drying it to obtain a clean sponge base.

7. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 1 or 6, characterized in that: In step S6, the clean sponge base is cut into cylinders with a radius of 0.5-2.5 cm and a height of 1-2 cm.

8. The method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to claim 7, wherein: In step S7, the amount of mixed solution B is 10-15 mL; the drying temperature is 40-60° C., and the drying time is 2-6 h.

9. Hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material, characterized in that: The material is prepared by the method for preparing the hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material according to any one of claims 1 to 8.

10. The use of the hydrophilic-hydrophobic anisotropic composite structure light-to-heat conversion material according to claim 9, characterized in that: The hydrophilic-hydrophobic anisotropic composite structure photothermal conversion material is applied in the fields of solar photothermal water evaporation, seawater desalination and antibacterial.